Examining access to care in clinical genomic research and medicine: Experiences from the CSER Consortium. Issue 1 (14th September 2021) - Gutierrez, Amanda M.; Robinson, Jill O.; Outram, Simon M.; Smith, Hadley S.; Kraft, Stephanie A.; Donohue, Katherine E.; Biesecker, Barbara B.; Brothers, Kyle B.; Chen, Flavia; Hailu, Benyam; Hindorff, Lucia A.; Hoban, Hannah; et al.
Abstract: Introduction: Ensuring equitable access to health care is a widely agreed-upon goal in medicine, yet access to care is a multidimensional concept that is difficult to measure. Although frameworks exist to evaluate access to care generally, the concept of "access to genomic medicine" is largely unexplored and a clear framework for studying and addressing major dimensions is lacking. Methods: Comprised of seven clinical genomic research projects, the Clinical Sequencing Evidence-Generating Research consortium (CSER) presented opportunities to examine access to genomic medicine across diverse contexts. CSER emphasized engaging historically underrepresented and/or underserved populations. We used descriptive analysis of CSER participant survey data and qualitative case studies to explore anticipated and encountered access barriers and interventions to address them. Results: CSER's enrolled population was largely lower income and racially and ethnically diverse, with many Spanish-preferring individuals. In surveys, less than a fifth (18.7%) of participants reported experiencing barriers to care. However, CSER project case studies revealed a more nuanced picture that highlighted the blurred boundary between access to genomic research and clinical care. Drawing on insights from CSER, we build on an existing framework to characterize the concept and dimensions of access to genomic medicine along with associated measures and improvement strategies. Conclusions: Our findings support adopting a broad conceptualization of access to care encompassing multiple dimensions, using mixed methods to study access issues, and investing in innovative improvement strategies. This conceptualization may inform clinical translation of other cutting-edge technologies and contribute to the promotion of equitable, effective, and efficient access to genomic medicine.